Reformulasi Strategi untuk Meningkatkan Budaya Keselamatan Kerja di PT XYZ - Tujuan Sanggam Silaen; Lukman M Baga; KirBrandoko KirBrandoko (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Upstream oil and gas sector has the characteristics of high-cost, high-tech and high-risk, and safety of operations. PT XYZ is a national company operating in the upstream oil and gas sector with operations spreading across Indonesia. This study aimed to evaluate the achievement of the current safety culture of the company, to analyze the behavioral factors that influenced safety culture and to redefine the strategy to improve the safety culture to minimize the occurrence of accidents. The research method used in the study included validity test and Reliability test, descriptive analysis, gap analysis and SEM analysis (Structural Equation Modelling). The results of the gap analysis show that safety culture in PT XYZ has not met the expectations. The results of the SEM analysis showed behavioral factors significantly influenced the safety culture. The combination between gap analysis and SEM Analysis showed that the strategies that should be carried out by PT XYZ in improving safety culture include strengthening the management commitment for safety, ensuring the process of investigation conducted objectively, maintaining the program rewards and consequences, writing safety aspects in the job description and job responsibilities and individual performance criteria, strengthening employee competence in occupational safety, intensifying communication of occupational safety aspects, analyzing workload and ensuring adequacy of the personnel number and application of SWA (stop work authority).Keywords: oil and gas, safety culture, SEM